A single multilocus sequence typing (MLST) scheme for seven pathogenic Leptospira species. - Siriphan Boonsilp; Janjira Thaipadungpanit; Premjit Amornchai; Vanaporn Wuthiekanun; Mark S Bailey; Matthew T G Holden; Cuicai Zhang; Xiugao Jiang; Nobuo Koizumi; Kyle Taylor; Renee Galloway; Alex R Hoffmaster; et al. (Public Library of Science (PLoS), 2013)
The available Leptospira multilocus sequence typing (MLST) scheme supported by a MLST website is limited to L. interrogans and L. kirschneri. Our aim was to broaden the utility of this scheme to incorporate a total of seven pathogenic species.We modified the existing scheme by replacing one of the seven MLST loci (fadD was changed to caiB), as the former gene did not appear to be present in some pathogenic species. Comparison of the original and modified schemes using data for L. interrogans and L. kirschneri demonstrated that the discriminatory power of the two schemes was not significantly different. The modified scheme was used to further characterize 325 isolates (L. alexanderi [n = 5], L. borgpetersenii [n = 34], L. interrogans [n = 222], L. kirschneri [n = 29], L. noguchii [n = 9], L. santarosai [n = 10], and L. weilii [n = 16]). Phylogenetic analysis using concatenated sequences of the 7 loci demonstrated that each species corresponded to a discrete clade, and that no strains were misclassified at the species level. Comparison between genotype and serovar was possible for 254 isolates. Of the 31 sequence types (STs) represented by at least two isolates, 18 STs included isolates assigned to two or three different serovars. Conversely, 14 serovars were identified that contained between 2 to 10 different STs. New observations were made on the global phylogeography of Leptospira spp., and the utility of MLST in making associations between human disease and specific maintenance hosts was demonstrated.The new MLST scheme, supported by an updated MLST website, allows the characterization and species assignment of isolates of the seven major pathogenic species associated with leptospirosis.